Studying of the Potential Curves of Ground State of Diatomic Molecule Using Two Functions. - Atiah, Asma S.; Abdullah, Muhaj T. (Science Journal of University of Zakho, 2015)
Diatomic molecules have been studied theoretically for ground state X2Π of (CH,CO,LuF,HBr) free radicals . It had been constructed dissociation energy using potential curves for the ground state by using Morse and Varshini functions to calculate potential curve for each molecule; compared between the results and experimental values had obtained. The results have good agreement with experimental results. Finding that Varshini function approximate with experimental values more than Morse function does.
Keywords: Diatomic; Morse function; Varshini function; potential curve